Remote monitoring of vital signs - Lambrinos, Lambros; Cristina, Stefania; Pocta, Peter; Camilleri, Kenneth; Zgank, Andrej; Colantonio, Sara (My University, 2025)
This chapter aims to explore state-of-the-art vision- and audio-based methods for vital sign monitoring, as applied to ambient assisted living for the older adults and people with special needs. We review different vision- and audio-based monitoring techniques, identify their advantages and limitations, explore emerging trends and open challenges, and draw recommendations for future directions. This work will serve as a starting point for beginners who are looking to gain an entry point into the area, as well as a guide to practitioners who are interested in learning more about recent developments of vision- and audio-based methods for active assisted living in general, and remote monitoring of vital signs in particular.
Keywords: Environmental Monitoring; Internet of Things; Media and Communication Methods; Motion Detection; Wearable Technology; Audio-Visual Culture